PERAN ORGANISME SESSILE SEBAGAI BIOINDIKATOR MIKROPLASTIK DI EKOSISTEM PESISIR: SYSTEMATIC LITERATURE REVIEW - Intan Feby Nasty; Sandi Fransisco Pratama (Universitas Cokroaminoto Palopo, 2026)
Microplastics have emerged as pervasive contaminants in coastal ecosystems and can accumulate in sessile organisms, particularly bivalves, through filtration mechanisms. This study aims to synthesize existing evidence on microplastic concentration, characteristics, polymer types, and identification methods in sessile organisms using a systematic literature review (SLR) approach. Literature selection was conducted following the PRISMA guidelines, with inclusion criteria limited to primary research articles published between 2015 and 2025. The synthesis results indicate that microplastics are consistently detected in sessile organisms, with concentrations varying among species and locations. Fibers represent the dominant microplastic shape, followed by fragments, while particle sizes are generally within smaller microplastic classes that exhibit high bioavailability. The most frequently identified polymer types include polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET), suggesting predominantly anthropogenic sources associated with domestic and fisheries-related activities. Across all reviewed studies, microplastic identification was primarily performed using spectroscopic techniques, particularly Fourier Transform Infrared Spectroscopy (FTIR) and its variants, which enable accurate polymer determination. Overall, this review highlights the potential of sessile organisms as effective bioindicators of microplastic pollution in coastal environments and underscores the need for standardized analytical methods to improve data comparability across studies.